Gamification in Marketing: Enhancing Customer Engagement through Interactive Experiences - Mar'atush Sholihah; Hasti Pramesti Kusnara; Diana Fitri Anggraini (Takaza Innovatix Labs Ltd., 2025)
This study investigates the role of gamification in enhancing customer engagement on TikTok among users in the Jakarta area, focusing on the effects of interactive experiences and customer motivation. Gamification, through game-like elements such as challenges, points, and rewards, has emerged as a powerful tool for fostering deeper brand engagement and loyalty. Utilizing a quantitative research method, data were collected through online surveys of 100 TikTok users, with the analysis conducted via Structural Equation Modeling (SEM). The results demonstrate that gamification significantly impacts both interactive experiences and customer motivation, which, in turn, positively influence customer engagement. Additionally, the study reveals that interactive experiences and customer motivation act as mediators between gamification and engagement, amplifying the effectiveness of gamified marketing strategies. These findings highlight the potential for brands to leverage gamification to create sustained emotional connections and long-term loyalty in fast-paced, short-form video platforms like TikTok. The study also emphasizes the importance of understanding local cultural and demographic factors in tailoring gamified marketing approaches for maximum impact.